1985
DOI: 10.1029/ja090ia02p01413
|View full text |Cite
|
Sign up to set email alerts
|

Solar wind decrease at high heliographic latitudes detected from Prognoz interplanetary lyman alpha mapping

Abstract: New evidence for a latitudinal decrease of the solar wind mass flux is presented from observations of the interplanetary Lyman alpha emission collected in 1976 and 1977 with satellites Prognoz 5 and 6. The flow of interstellar hydrogen atoms in the solar system is ionized by EUV solar radiation and charge exchange with solar wind protons which accounts for about 80% of the total ionization rate. The resulting gradual decrease of the neutral H density from the upwind region down to the downwind region observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(49 citation statements)
references
References 12 publications
4
44
1
Order By: Relevance
“…Hence, if the flux of the solar wind is higher at the solar equator than at the poles, then the ionization rate in the equatorial region is enhanced and a depression in the distribution of interplanetary hydrogen can be expected (Joselyn & Holzer 1975;Summanen et al 1993;Lallement et al 1995;Bertaux et al 1996a;Summanen 1996). Such a depression, referred to as the heliospheric groove, was indeed observed in some observations of the heliospheric backscatter Lyman-α glow, but it was absent in some others (Ajello 1990;Ajello et al 1987Ajello et al , 1993Bertaux et al 1996b;Lallement et al 1985bLallement et al , 1995Lallement & Stewart 1990;Pryor et al 1992Pryor et al , 1996Pryor et al , 1998. Based on these scarce observations it was hypothesized that the groove appears during solar minimum and disappears during maximum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, if the flux of the solar wind is higher at the solar equator than at the poles, then the ionization rate in the equatorial region is enhanced and a depression in the distribution of interplanetary hydrogen can be expected (Joselyn & Holzer 1975;Summanen et al 1993;Lallement et al 1995;Bertaux et al 1996a;Summanen 1996). Such a depression, referred to as the heliospheric groove, was indeed observed in some observations of the heliospheric backscatter Lyman-α glow, but it was absent in some others (Ajello 1990;Ajello et al 1987Ajello et al , 1993Bertaux et al 1996b;Lallement et al 1985bLallement et al , 1995Lallement & Stewart 1990;Pryor et al 1992Pryor et al , 1996Pryor et al , 1998. Based on these scarce observations it was hypothesized that the groove appears during solar minimum and disappears during maximum.…”
Section: Introductionmentioning
confidence: 99%
“…However, already early observations revealed that this was not always the case. It was hypothesized that the non-cylindrical distribution of the Lyman-α heliospheric glow was due to a departure of the solar wind from spherical symmetry (Kumar & Broadfoot 1978, 1979Witt et al 1979Witt et al , 1981Lallement et al 1985b). It was further proposed that the latitudinal structure of the solar wind was connected with the heliospheric current sheet (Bertaux et al 1996a).…”
Section: Introductionmentioning
confidence: 99%
“…This model is based on the hot model developed by Lallement et al [1985] with corrections for an anisotropic ionization rate and any values for the radiation pressure coefficient . An actual solar line profile derived from the SUMER/SOHO measurements [Lemaire et al, 2002] is used.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Lallement et al [1985] analyzed the interplanetary Lyman data recorded by the Prognoz 5/6 Lyman photometers in 1976 and 1977. They showed that the Lyman intensity pattern was better represented when an anisotropic ionization flux from the Sun was assumed.…”
Section: Introductionmentioning
confidence: 99%
“…Basically, this function is quite complicated since the hydrogen gas is heavily processed by the heliospheric interface (Izmodenov et al 2001). In practice, it is assumed that the gas distribution function at r ∞ is a Maxwellian with a temperature T ∞ , travelling with the bulk velocity vector u B (see also Fahr 1978;Thomas 1978;Wu & Judge 1979;Lallement et al 1985; and a review by Ruciński & Bzowski 1996). The velocity vector u 0 of the atom at r ∞ is calculated numerically by back-tracking the atom from its position (r, θ, δ) inside the heliosphere, where it has velocity vector equal to u, to r ∞ .…”
Section: Modelingmentioning
confidence: 99%